Antioxidant and anti-proliferative activities of Sabah Ruellia tuberosa - Bo Eng Cheonga, Mohd. Zulkarnain Waslimb, Fui Fui Lema, Peik Lin Teoha (Journal of Applied Pharmaceutical Science, 2013)
The study was carried out to evaluate the total phenolic constituents, antioxidant and anti-proliferative activities of Sabah Ruellia tuberosa. The total phenolic and flavonoid contents of the plant extracts were determined by using Folin-Ciocalteau and aluminium chloride colorimetric assays, respectively. The antioxidant activity of the plant extracts was evaluated using DPPH free radical scavenging assay while the anti-proliferative activity was evaluated using MTT assay against the human breast cancer (MCF-7) and cervical cancer (HeLa) cell lines. The methanol leaf extract was found to possess the highest total phenolic content (82.67 ± 2.09 mg GAE/g) while the ethyl acetate leaf extract was found to possess the highest total flavonoid content (152.77 ± 4.68 mg Cat/g). The ethyl acetate leaf possessed the highest radical scavenging activity, with IC50 of 720 μg/ml. Meanwhile, the methanol stem extract showed the highest anti-proliferative activity against MCF-7 cancer cells, with IC50 of 22 μg/ml but none of the extracts exhibited strong anti-proliferative activity against the HeLa cancer cell lines. Significant correlation was found between the total phenolic/flavonoid contents with the total antioxidant activity while weak correlation was found between the total phenolic/flavonoid contents with the inhibition of MCF-7 cell proliferation. Our findings indicate that Sabah Ruellia tuberosa could be a potential source for natural antioxidant as well as chemo-preventive agent against breast cancer in future. Thus, further isolation and characterization of the respective bioactive compounds from the plants are necessary.
Keywords: Ruellia tuberosa,antioxidant activity, anti-proliferative activity.